2020
DOI: 10.1186/s12888-020-02743-5
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted brain network dynamics and cognitive functions in methamphetamine use disorder: insights from EEG microstates

Abstract: Background Dysfunction in brain network dynamics has been found to correlate with many psychiatric disorders. However, there is limited research regarding resting electroencephalogram (EEG) brain network and its association with cognitive process for patients with methamphetamine use disorder (MUD). This study aimed at using EEG microstate analysis to determine whether brain network dynamics in patients with MUD differ from those of healthy controls (HC). Methods A total of 55 MUD patients and 27 matched heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 76 publications
0
8
1
Order By: Relevance
“…For example, Meth-dependent patients showed a higher coverage of class A compared to HCs, along with a lower coverage and occurrence of class B. Although the discussion of between-group differences in the resting state is beyond the scope of this study, we found that these findings are mostly inconsistent with the previous study by Chen et al ( 34 ). In their study, they reported that Meth-dependent patients showed a lower duration of the microstate classes A and B, compared to HCs.…”
Section: Discussioncontrasting
confidence: 92%
“…For example, Meth-dependent patients showed a higher coverage of class A compared to HCs, along with a lower coverage and occurrence of class B. Although the discussion of between-group differences in the resting state is beyond the scope of this study, we found that these findings are mostly inconsistent with the previous study by Chen et al ( 34 ). In their study, they reported that Meth-dependent patients showed a lower duration of the microstate classes A and B, compared to HCs.…”
Section: Discussioncontrasting
confidence: 92%
“…For example, the risk of relapse may increase after stimulation by drug-related cues. One alternative approach has been recorded, brain signals when participants are involved in cognitive tasks, to differentiate those suffering from an addiction from healthy controls (32); for example, in one study, EEG signals were analyzed when patients with METH addiction performed cognitive tasks, including the N-back task to assess working memory and Stroop task to assess attention (102).…”
Section: Stimulation Cuesmentioning
confidence: 99%
“…Other EEG biomarkers represented by topography include EEG microstates that show the spatial distribution of electrical signals recorded by the electrodes over the scalp (102,118). The dynamic changes of these electric potential states can be validated by examining a consecutive set of topographies.…”
Section: Biomarkers Of Eeg and Fnirs In Meth Addictionmentioning
confidence: 99%
“…In recent years, EEG microstate analysis has been used in patients with mental disorder, such as bipolar disorder (26), methamphetamine use disorder (27), schizophrenia (28), and depression (21,22). Different psychopathological conditions showed different EEG microstate feature changes.…”
Section: Introductionmentioning
confidence: 99%